Mastiff [compact disc, unabridged] - Pierce, Tamora (Pierce, Tamora. Beka Cooper, 2011)
The Legend of Beka Cooper gives Tamora Pierce's fans exactly what they want, a smart and savvy heroine making a name for herself on the mean streets of Tortall's Lower City, while offering plenty of appeal for new readers as well.